First record of Myriostoma (Geastraceae, Basidiomycota) in the Parque Estadual das Fontes do Ipiranga (PEFI), São Paulo, São Paulo State, Brazil - Trierveiler-Pereira, Larissa (2020)
Myriostoma is an easily identifiable genus due to its basidiome with multiple stalks and ostioles in the endoperidium. Its occurrence in South America is limited to Brazil and Argentina, but the basidiomes are not abundant and easily found in nature. The aim of this study is to report for the first time the occurrence of Myriostoma calongei in the Parque Estadual das Fontes do Ipiranga, São Paulo, since the genus was reported only once from the State.